Degradation of ofloxacin by a manganese-oxidizing bacterium Pseudomonas sp. F2 and its biogenic manganese oxides. (May 2021) - Li, Kangjie; Xu, Anlin; Wu, Donghong; Zhao, Siyan; Meng, Tong; Zhang, Yongjun
Graphical abstract: Highlights: Pseudomonas sp. F2 can effectively degrade OFL. The stepwise dosage of Mn(II) can enhance the degradation. The active metabolism of Mn(II) and the Mn(III) intermediates play important roles. The transformation products and the possible degradation pathway were proposed. The toxicity of OFL can be reduced by 66% after the degradation. Abstract: Fluoroquinolone antibiotics like ofloxacin (OFL) have been frequently detected in the aquatic environment. Recently manganese-oxidizing bacteria (MOB) have attracted research efforts on the degradation of recalcitrant pollutants with the aid of their biogenic manganese oxides (BioMnOx). Herein, the degradation of OFL with a strain of MOB ( Pseudomonas sp. F2) was investigated for the first time. It was found that the bacteria can degrade up to 100% of 5 μg/L OFL. BioMnOx and Mn(III) intermediates significantly contributed to the degradation. Moreover, the degradation was clearly declined when the microbial activity was inactivated by heat or ethanol, indicating the importance of bioactivity. Possible transformation products of OFL were identified by HPLC-MS and the degradation pathway was proposed. In addition, the toxicity of OFL was reduced by 66% after the degradation.